Case Report: First Case of Endophthalmitis Caused by an Emerging Pathogen: Nocardia huaxiensis - Liu, Chang; Zhang, Lei; Liu, Lili; Wang, Ye; Cui, Yanhui; Liang, Tianwei; Chen, Tianming; Jiang, Yongqiang; Liu, Gang; Li, Li (Frontiers in Public Health, 2022)
Nocardia endophthalmitis is a relatively uncommon form of endophthalmitis seen in clinical patients. In general, Nocardia endophthalmitis tends to carry a poor prognosis. Here, we report a 3-year-old child who was admitted to the hospital due to a rupture of the left eye. The suturing and anterior chamber formation were performed immediately. Approximately, 16 days after the operation, massive whitish plump and tufted exudates gathered in the pupil area and at the bottom of the anterior chamber, and the child was diagnosed with endophthalmitis. The infection was initially considered to be caused by fungal pathogens for that the hyphae and spores were observed in the smear. However, the isolate obtained after 4 days of culturation was identified as actinomycetes using MALDI–TOF. We further classified it as Nocardia huaxiensis by next-generation sequencing (NGS) based on the MinION platform. Amikacin and sulfamethoxazole tablets were used to control the infection and the ocular inflammation subsided gradually. Intraocular lens (IOL) implantation is planned to be performed at an appropriate future time to improve his vision. Nocardia endophthalmitis is rare and usually caused by ocular trauma or surgery. In conclusion, Nocardia huaxiensis should be considered as an emerging pathogen and deserves more attention.